Genome-wide search for copy number variations associated with blood parameters in Large White pigs - M. A. Kolosova; L. V. Getmantseva; S. Yu. Bakoev; A. Yu. Kolosov (Аграрная наука Евро-Северо-Востока)
Copy number variations (CNVs) are repetitive regions of the genome, ranging from one thousand to several million base pairs in size, that vary between individuals in a population. Due to their greater genome coverage compared to SNPs (single nucleotide polymorphisms), CNVs are an important source of genetic variability and are currently considered an alternative type of DNA marker. To date, there are studies in animal husbandry indicating the effect of CNVs on phenotypic variability. However, few studies have focused on the associations of CNVs with blood parameters, which could help identify subtle mechanisms underlying the physiological regulation of phenotypes associated with health and selection-important traits. The aim of this work was to identify CNVs associated with alanine aminotransferase (ALT), urea (Urea), red blood cell (RBC) and white blood cell (WBC) counts in Large White pigs and to identify candidate genes that may be considered as genetic markers in hematopoietic functions, physiological processes and productivity phenotypes. The study was conducted on Large White pigs. Genotyping was performed using the GGP Porcine HD Genomic Profiler v1 biochip containing 80,000 SNPs. Functional annotation was performed according to the Sscrofa11.1 assembly using the Ensembl Genome Browser.  As a result of the study, CNVs (deletions/duplications) associated with ALT, Urea, RBC, and WBC levels were identified in Large White pigs. Genes overlapping CNV regions associated with the studied blood parameters in pigs were identified: ALT (BBS9, TTC14, KCND3, TRPC1, PSMD1, MMP16, KCNJ3, ADAM2); Urea (ESR1, USP8, CAST, CNBD1); RBC (PSMD1, TTC14, FUT8, CSMD3); WBC (BBS9, KCND3, BMPR2). According to the functional annotation, these genes can be considered promising genetic markers for hematopoietic functions, physiological processes, and productivity phenotypes in pigs.